Correlational analysis of the dependence of the health of the population of Ukraine on smoking as a factor in the development of diseases (Environment & Health, 2024)
Numerous clinical studies have established that smoking has a harmful effect on human health including diabetes mellitus. The aim is to assess the peculiarities of health changes among citizens of Ukraine under the influence of a harmful factor, thanks to a simultaneous questionnaire and in-depth medical examination for further improvement of diagnostics and stratification of the degree of risk of developing various diseases and timely appointment of adequate therapy.Materials and methods. Among the laboratory tests, the following were determined: blood glucose level, IR marker – Нoma index, which were determined on an empty stomach, in the morning, the last meal was 12 hours before blood donation. Determination of the results of indicators was carried out using chemiluminescence analysis. Reagents: Roche Diagnostics (Switzerland). Analyzer Cobas 8000 | ProCobas 6000 |Cobas 411 (Switzerland). Statistical data processing was carried out using a software package. The relationship between quantitative indicators was carried out using Pearson’s correlation analysis (r ). Statistical probability was estimated by the parametric Student’s t-test. The difference was considered probable at p
Keywords: smoking; type 2 diabetes; prediabetes; insulin resistance; Homa index; cardiovascular diseases; state of health